Laminated polyester film and coating composition

A laminated polyester film with a resin layer containing polystyrene sulfonic acid and acrylic resin maintains durable antistatic properties, addressing wear and surface treatment issues, ensuring effective use in cover tapes and protective films.

JP7622431B2Active Publication Date: 2025-01-28TORAY INDUSTRIES INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020537252
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-22
Filing Date
2020-06-05
Publication Date
2025-01-28
Estimated Expiration
2040-06-05

AI Technical Summary

Technical Problem

Existing two-axis-oriented polyester films lack durable antistatic properties, which deteriorate due to wear and surface treatments, affecting their performance in applications like cover tapes for electronic components.

Method used

A laminated polyester film with a resin layer containing polystyrene sulfonic acid and/or its salt, acrylic resin, and a multi-alcohol compound, having a surface resistance of 10^6 to 10^12 Ω/□, and a wear ratio of 5.0 or less, is developed to maintain antistatic properties during wear and corona discharge treatments.

Benefits of technology

The laminated film maintains excellent antistatic properties, preventing electrical destruction and ensuring transparency, even after wear and surface treatments, making it suitable for cover tapes and protective films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622431000001
    Figure 0007622431000001
  • Figure 0007622431000002
    Figure 0007622431000002
  • Figure 0007622431000003
    Figure 0007622431000003
Patent Text Reader

Abstract

A multilayer polyester film according to the present invention comprises a polyester film and a resin layer (X); and at least a surface layer on one side thereof is composed of the resin layer (X). With respect to this multilayer polyester film, the surface resistivity (RX) of the resin layer (X) is from 106 Ω / □ to 1012 Ω / □, and the ratio of the surface resistivity (RY) of the resin layer (X) after having the surface of the resin layer (X) subjected to an abrasion treatment under the conditions described below to the surface resistivity (RX), namely RY / RX is 5.0 or less. Another multilayer polyester film according to the present invention comprises a polyester film and a resin layer (X); and at least a surface layer on one side thereof is composed of the resin layer (X). With respect to this multilayer polyester film, the resin layer (X) contains (A) a resin component, (B) a polystyrene sulfonic acid and / or a salt thereof, and (C) a polyhydric alcohol; and the glass transition temperature of the resin component (A) is from 40°C to 120°C (inclusive). The multilayer polyester films according to the present invention have excellent antistatic properties that are not likely to deteriorate due to abrasion during conveyance in processing steps or a surface treatment such as a corona discharge treatment. The multilayer polyester films according to the present invention are able to be used as protection films that are used for electronic components or the like, and are especially suitable for use in cover tapes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated polyester film having a polyester film and a resin layer, and a coating composition. [Background technology]

[0002] Thermoplastic resin films, particularly biaxially oriented polyester films, have excellent properties such as mechanical properties, electrical properties, dimensional stability, transparency, and chemical resistance, and are therefore widely used in many applications such as magnetic recording materials and packaging materials.

[0003] However, since polyester is generally an insulating resin, biaxially oriented polyester films have the disadvantage that they do not have antistatic properties as they are. Antistatic properties are properties that are imparted in order to suppress foreign matter defects caused by dust adhesion due to charging, and can be imparted, for example, by neutralizing the bias of electric charge by imparting electrical conductivity to the surface or inner layer of an insulating material such as a biaxially oriented polyester film. Among these, the method of imparting antistatic properties by providing a conductive coating layer on the surface of a polyester film makes it easy to maintain various stable properties of the film, and various methods have been studied in the past.

[0004] As a conventional method for imparting antistatic properties, a method of applying a styrene sulfonic acid copolymer, which is an ion-conductive antistatic agent, to a polyester resin (see, for example, Patent Document 1) and a technology focusing on the dispersibility of a styrene sulfonic acid copolymer and an acrylic resin for the purpose of further improving functionality (Patent Document 2) have been proposed. On the other hand, a method of combining an epoxy crosslinking agent with a polythiophene-based conductive agent, which is an electron-conductive antistatic agent, to achieve both transparency and antistatic properties of the coating film has been proposed (Patent Document 3). In addition, a technology of combining a polythiophene-based conductive agent with a hydroxyl group-containing compound for the purpose of improving antistatic properties (Patent Document 4) and a technology of imparting durability to a boiling resistance test using a polythiophene-based conductive agent have been proposed (Patent Document 5).

[0005] The antistatic method disclosed in Patent Document 1, which uses an ion-conductive type antistatic agent, and the improved method disclosed in Patent Document 2, have insufficient antistatic properties and are prone to losing performance due to wear.

[0006] On the other hand, the method described in Patent Document 3 and the improved techniques described in Patent Documents 4 and 5 have problems such as insufficient antistatic properties during corona discharge treatment described below, the antistatic component being particularly noticeable because of its dark navy blue color, and affecting the characteristics in terms of quality control.

[0007] In addition, the combined use of the "acrylic resin" of Patent Document 2 and the "hydroxy group-containing compound having three or more hydroxy groups" of Patent Document 4 is effective in improving the initial antistatic property, but is poor in preventing the deterioration of the antistatic property described below.

[0008] The biaxially oriented polyester film having antistatic properties is used for a protective film for electronic parts, etc. The main application of the protective film is as a cover tape.

[0009] Here, the problems of the cover tape of electronic components will be described in particular. When the cover tape is peeled off from the electronic components, the electronic components may inadvertently fly out due to the peeling charge of the cover tape, resulting in the electronic components being scattered, or a discharge may occur between the charged tape and the electronic components, resulting in the electronic components being electrically destroyed. When the electronic components are packaged with the cover tape and carrier tape, the electronic components are inspected from the cover tape side. The inspection of the electronic components includes, for example, an inspection to check whether different types are mixed in, whether the lead terminals of the IC chip are bent, or whether the filling direction is incorrect. In order to easily perform these inspections, the cover tape needed to be highly transparent. The cover tape used was made of a highly transparent transparent polyester film or transparent polyolefin film that had been antistatically treated.

[0010] However, in the process of producing the cover tape, multiple layers such as a primer and a sealant are formed on the conductive polyester film substrate, and the antistatic properties are reduced due to friction during the processing. Furthermore, as exemplified in Patent Document 6, surface treatment such as discharge treatment may be performed to increase the adhesion between the polyester film substrate and the sealant, but when surface treatment such as discharge treatment is performed to increase the adhesion between the polyester film substrate and the sealant, the antistatic performance is reduced. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Japanese Patent Publication No. 61-204240 [Patent Document 2] JP 2003-071995 A [Patent Document 3] JP 2004-58648 A [Patent Document 4] JP 2016-047881 A [Patent Document 5] JP 2016-064625 A [Patent Document 6] JP 2010-013135 A Summary of the Invention [Problem to be solved by the invention]

[0012] Therefore, the present invention provides a laminated film that overcomes the above-mentioned drawbacks and can be suitably used for a protective film, particularly a cover tape. [Means for solving the problem]

[0013] In order to solve the above problems, the present invention has the following configuration.

[0014] (1) A laminated polyester film having a polyester film and a resin layer (X), the laminate having the resin layer (X) on at least one surface layer,the resin layer (X) has a resin component (A), the glass transition temperature (Tg) of the resin component (A) is 46°C or more and 120°C or less, the resin component (A) is an acrylic resin, the resin layer (X) further has polystyrene sulfonic acid and / or a salt thereof (B), the amount of polystyrene sulfonic acid and / or a salt thereof (B) in the resin layer (X) is 15 mass% or more and 50 mass% or less, Surface resistivity of the resin layer (X) (R X ) is 10 6 Ω / □ or more, 10 12 Ω / □ or less, R X and the surface resistivity (R Y ) and R Y / R X The value of 5.0 The laminated polyester film is as follows: [Wear treatment conditions] The resin layer (X) surface of the laminated polyester film is subjected to a load of 20 g / cm 2 The surface of the resin layer (X) is abraded ten times with a nonwoven fabric (Hi-Ze Gauze NT-4 manufactured by Ozu Sangyo Co., Ltd.).

[0016] ( 2 )(1 )of Cover tape made of laminated polyester film.

[0017] ( 3 )(1 ) The method for producing the laminated polyester film described above includes a step of applying a coating composition to at least one side of a polyester film, followed by a stretching treatment and a heat treatment in at least one direction, wherein the coating composition contains polystyrene sulfonic acid and / or a salt thereof (B). Effect of the Invention

[0019] The laminated polyester film of the present invention has excellent antistatic properties and is not easily deteriorated by abrasion during transportation in the processing step or by surface treatment such as corona discharge treatment, etc. The laminated polyester film of the present invention can be used as a protective film for electronic parts, etc., and is particularly suitable for use as a cover tape. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The laminated polyester film of the present invention will be described in detail below.

[0021] The laminated polyester film of the present invention is a laminated polyester film having a polyester film and a resin layer (X), which has a resin layer (X) on at least one surface layer, and the surface resistivity (R X ) is 10 6 Ω / □ or more, 10 12 Ω / □ or less, R X and the surface resistivity (R Y ) and R Y / R X The abrasion treatment here refers to a process in which the surface of the resin layer (X) of the laminated polyester film is subjected to a load of 20 g / cm 2 This indicates that the surface of the resin layer (X) is abraded 10 times using a nonwoven fabric (Hi-Ze Gauze NT-4 manufactured by Ozu Sangyo Co., Ltd.).

[0022] Surface resistivity of the resin layer (X) (R X ) but 10 6 Ω / □ or more, 10 12 When the surface resistivity is Ω / □ or less, the laminated polyester film has high antistatic properties. Y / R X If the value of R is 5.0 or less, the deterioration of antistatic performance due to abrasion during transportation can be suppressed. Y / R X If the value exceeds 5.0, the antistatic properties gradually decrease, which is problematic in practical use.

[0023] In addition, when the laminated polyester film is used for a cover tape, the antistatic properties are reduced due to friction during the processing step in which multiple layers such as primer and sealant are formed in the process of producing the cover tape. Y / R XThe surface resistivity (R) of the resin layer (X) can be reduced by, for example, adjusting the amount of the crosslinking component in the coating composition forming the resin layer (X), the compounding ratio and material type of the conductive material and the crosslinking component, controlling the dispersion state of the conductive component by controlling drying and stretching, and combining the material type and preparation conditions such as the coating thickness and surface shape. X ) is 1.5 × 10 6 Ω / □ or more, 5.0×10 9 It is preferable that R Y / R X is preferably 4.5 or less, more preferably 3.0 or less, and even more preferably 1.0 or more and 2.0 or less.

[0024] Furthermore, the laminated polyester film of the present invention has a surface resistivity (R X ) and the surface resistivity (R Z ) and the ratio R Z / R X It is preferable that the ratio R is 10.0 or less. Z / R X If R exceeds 10.0, it may be difficult to achieve both adhesion between the polyester film and various functional layers and antistatic properties. Here, the corona discharge treatment refers to placing the laminated polyester film on an earth plate with the resin layer (X) facing upward, and performing corona discharge treatment on the side opposite to the side having the resin layer (X) with a corona discharge treatment output of 100 W, a discharge gap with the ceramic electrode of 1 mm, an electrode moving speed of 1 m / min, and a treatment number of 1. The corona discharge treatment can be performed, for example, using a corona surface modification evaluation device TEC-4AX manufactured by Kasuga Electric Co., Ltd. Z / R X The value of can be reduced by, for example, selecting an appropriate conductive material type to be contained in the resin layer (X), controlling the compounding ratio of the crosslinking component in the coating composition forming the resin layer (X), controlling the dispersion state of the conductive component by controlling drying and stretching, controlling the coating thickness and the uneven distribution state in the thickness direction, etc. X) and the surface resistivity (R Z ) and the ratio R Z / R X is more preferably 5.0 or less, even more preferably 3.0 or less, and particularly preferably 1.0 or more and 2.0 or less.

[0025] The resin layer (X) of the laminated polyester film of the present invention preferably has an average surface roughness Ra measured within a 1 μm square range of 3 nm to 10 nm. When Ra is less than 3 nm, the slipperiness of the resin layer (X) is insufficient, and the antistatic properties may be easily reduced due to the insufficient slipperiness, which may promote wear of the surface of the resin layer (X). On the other hand, when it exceeds 10 nm, transparency may be reduced. Examples of methods for controlling the centerline average surface roughness Ra of the resin layer (X) include a method of adding a particulate material to the resin layer (X), a method of adding particles to the polyester substrate, and a method of giving a shape to the surface by controlling the drying and stretching of the resin layer. As a method for controlling the centerline average surface roughness Ra of the resin layer (X), from the viewpoint of maintaining the wear resistance of the coating film, a method of adding particles to the polyester substrate and a method of giving a shape to the surface by controlling the drying and stretching of the resin layer are preferable.

[0026] Furthermore, the dynamic friction coefficient between the resin layer (X) surface of the laminated polyester film of the present invention and its opposite surface is preferably 0.5 or less. If the dynamic friction coefficient exceeds 0.5, the slipperiness may be insufficient, and the antistatic property may be easily deteriorated. The lower limit is not particularly limited, but the practical measurement lower limit is about 0.01. The details of the method for measuring the dynamic friction coefficient will be described later. The dynamic friction coefficient between the resin layer (X) surface of the laminated polyester film of the present invention and its opposite surface is more preferably 0.05 or more and 0.4 or less.

[0027] The resin layer (X) of the laminated polyester film of the present invention preferably contains a resin component (A).

[0028] The resin used as the resin component (A) preferably has a glass transition temperature (Tg) of 40° C. to 120° C., more preferably 60° C. to 120° C., and particularly preferably 70° C. to 120° C. By making the glass transition temperature (Tg) of the resin component (A) 40° C. to 120° C., it becomes possible to maintain the hardness of the coating film in the actual usage environment, and the ratio R of the surface resistivity before and after the abrasion treatment becomes Y / R X and the ratio of surface resistivity before and after corona discharge treatment Rz / R X It is easy to adjust the value of Tg. Furthermore, when the resin layer (X) is produced by an in-line coating method, deterioration of the quality due to cracks, etc. can be eliminated. The method for measuring the glass transition temperature (Tg) will be described later.

[0029] Examples of the resin used as the resin component (A) include acrylic resin, polyester resin, polyurethane resin, melamine resin, and epoxy resin, and one or more of them can be used in combination. The ratio of surface resistivity values ​​before and after the abrasion treatment R Y / R X The value of , and the ratio of surface resistivity values ​​before and after corona discharge treatment R z / R X From the viewpoint of adjusting the value, acrylic resin, polyester resin, and polyurethane resin are preferred, and acrylic resin is particularly preferred.

[0030] As the acrylic resin, for example, an acrylic resin emulsion dispersed in water can be used, and the dispersion diameter is preferably 20 to 200 nm, more preferably 30 to 100 nm. If the dispersion diameter of the acrylic resin emulsion dispersed in water is 20 to 200 nm, it is desirable in terms of finely dispersing other resins. In order to obtain a dispersion diameter of less than 20 nm, it is necessary to use a large amount of emulsifier due to the specific surface area when preparing the acrylic emulsion by emulsion polymerization, etc., which may cause problems in adhesiveness, etc. If it exceeds 200 nm, fine dispersion may be difficult.

[0031] The monomer components constituting the acrylic resin are not particularly limited, and examples thereof include alkyl acrylates, alkyl methacrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, lauryl, stearyl, cyclohexyl, phenyl, benzyl, and phenylethyl groups), hydroxyl group-containing monomers such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, and 2-hydroxypropyl methacrylate, acrylamide, methacrylamide, N-methylacrylamide, N-methylmethacrylamide, and N-methylethylmethacrylamide. Amide group-containing monomers such as N-methylol acrylamide, N-methylol methacrylamide, N,N-dimethylol acrylamide, N-methoxymethyl acrylamide, N-methoxymethyl methacrylamide, and N-phenyl acrylamide, amino group-containing monomers such as N,N-diethylaminoethyl acrylate and N,N-diethylaminoethyl methacrylate, epoxy group-containing monomers such as glycidyl acrylate and glycidyl methacrylate, and monomers containing carboxyl groups or their salts such as acrylic acid, methacrylic acid, and their salts (lithium salt, sodium salt, potassium salt, etc.), can be used, and these can be copolymerized using one or more kinds. Furthermore, these can be used in combination with other types of monomers.

[0032] Examples of other types of monomers that can be used here include epoxy group-containing monomers such as allyl glycidyl ether, monomers containing carboxyl groups or their salts such as crotonic acid, itaconic acid, maleic acid, fumaric acid, and salts thereof (lithium salts, sodium salts, potassium salts, ammonium salts, etc.), monomers containing acid anhydrides such as maleic anhydride and itaconic anhydride, vinyl isocyanate, allyl isocyanate, styrene, vinyl methyl ether, vinyl ethyl ether, vinyl trisalkoxysilane, alkyl maleic acid monoester, alkyl fumaric acid monoester, acrylonitrile, methacrylonitrile, alkyl itaconic acid monoester, vinylidene chloride, vinyl chloride, vinyl acetate, etc. Modified acrylic copolymers, such as block copolymers and graft copolymers modified with polyester, urethane, and epoxy, can also be used.

[0033] The preferred acrylic resin used in the present invention is a copolymer selected from methyl methacrylate, ethyl acrylate, n-butyl acrylate, 2-hydroxyethyl acrylate, acrylamide, N-methylolacrylamide, acrylic acid, etc. As the polymerization method for the acrylic resin emulsion in the present invention, emulsion polymerization, suspension polymerization, etc. are usually preferably used.

[0034] The polyester resin used as the resin component (A) in the present invention has an ester bond in the main chain or side chain and is obtained by polycondensation of a dicarboxylic acid and a diol. The carboxylic acid component constituting the polyester resin can be an aromatic, aliphatic, or alicyclic dicarboxylic acid or a trivalent or higher polycarboxylic acid.

[0035] Examples of aromatic dicarboxylic acids that can be used include terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 2,5-dimethylterephthalic acid, 1,4-naphthalenedicarboxylic acid, biphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,2-bisphenoxyethane-p,p'-dicarboxylic acid, phenylindanedicarboxylic acid, and ester-forming derivatives thereof. Examples of aliphatic and alicyclic dicarboxylic acids that can be used include succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, dimer acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and ester-forming derivatives thereof.

[0036] The glycol components of the polyester resin include ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 2,4-dimethyl-2-ethylhexane-1,3-diol, neopentyl glycol, 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2,4 4,4'-trimethyl-1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 4,4'-thiodiphenol, bisphenol A, 4,4'-methylenediphenol, 4,4'-(2-norbornylidene)diphenol, 4,4'-dihydroxybiphenol, o-, m-, and p-dihydroxybenzene, 4,4'-isopropylidenephenol, 4,4'-isopropylidenebindiol, cyclopentane-1,2-diol, cyclohexane-1,2-diol, cyclohexane-1,4-diol, and the like can be used.

[0037] The polyester resin used as the resin component (A) in the present invention is preferably used as an aqueous liquid dissolved or dispersed in water. In order to facilitate the water solubility or water dispersion of the polyester resin, it is preferable to copolymerize a compound containing a sulfonate group or a compound having a hydrophilic group containing a carboxylate group.

[0038] Examples of compounds containing a sulfonate group include alkali metal salts, alkaline earth metal salts, and ammonium salts of sulfoterephthalic acid, 5-sulfoisophthalic acid, 4-sulfoisophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, sulfo-p-xylylene glycol, and 2-sulfo-1,4-bis(hydroxyethoxy)benzene.

[0039] Examples of compounds containing a carboxylate group include alkali metal salts, alkaline earth metal salts, and ammonium salts of trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, 4-methylcyclohexene-1,2,3-tricarboxylic acid, trimesic acid, 1,2,3,4-butanetetracarboxylic acid, 1,2,3,4-pentanetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, cyclopentanetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 1,2,5,6-naphthalenetetracarboxylic acid, ethylene glycol bistrimellitate, 2,2',3,3'-diphenyltetracarboxylic acid, thiophene-2,3,4,5-tetracarboxylic acid, and ethylenetetracarboxylic acid.

[0040] The polyester resin used as the resin component (A) in the present invention may be a modified polyester copolymer, for example, a block copolymer or a graft copolymer modified with acrylic, urethane, epoxy, or the like.

[0041] The polyester resin used as the resin component (A) can be produced by a method of directly esterifying a dicarboxylic acid component with a glycol component, or by polycondensing the reaction product of an ester exchange reaction, etc. In this case, for example, an alkali metal, an alkaline earth metal, manganese, cobalt, zinc, antimony, germanium, titanium compound, etc. can be used as a reaction catalyst.

[0042] The intrinsic viscosity of the polyester resin used as the resin component (A) is preferably 0.3 dl / g or more, more preferably 0.35 dl / g or more, from the viewpoint of adhesiveness.

[0043] The polyurethane resin used as the resin component (A) in the present invention is, for example, a water-soluble or water-dispersible polyurethane resin having an anionic group, and the main constituent component has a basic structure that is a reaction product of a polyol compound and a polyisocyanate compound.

[0044] Examples of polyol compounds that can be used include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene glycol, hexamethylene glycol, hexamethylene glycol, tetramethylene glycol, 1,5-pentanediol, diethylene glycol, triethylene glycol, polycaprolactone, polyhexamethylene adipate, polytetramethylene adipate, trimethylolpropane, trimethylolethane, glycerin, and acrylic polyols.

[0045] Examples of the polyisocyanate compound that can be used include tolylene diisocyanate, hexamethylene diisocyanate, phenylene diisocyanate, diphenylmethane diisocyanate, an adduct of tolylene diisocyanate and trimethylolpropane, and an adduct of hexamethylene diisocyanate and trimethylolethane.

[0046] The main components of the polyurethane resin may contain, in addition to the polyol compound and the polyisocyanate compound, a chain extender or a crosslinking agent, etc. Examples of the chain extender or crosslinking agent that can be used include ethylene glycol, propylene glycol, butanediol, diethylene glycol, ethylenediamine, and diethylenetriamine.

[0047] The anionic group in the polyurethane resin used as the resin component (A) may be a carboxylic acid group, a sulfonic acid group, or a sulfuric acid half ester group, or an ammonium salt, lithium salt, sodium salt, potassium salt, etc. of these. Sulfonic acid and / or a sulfonate group are particularly preferred.

[0048] The amount of anionic groups in the polyurethane resin used as the resin component (A) is preferably from 0.05% by weight to 15% by weight from the viewpoint of suppressing blocking.

[0049] The polyurethane resin having an anionic group can be produced, for example, by using a compound having an anionic group in a polyol, a polyisocyanate, a chain extender, or the like; by reacting an unreacted isocyanate group in the produced urethane resin with a compound having an anionic group; or by reacting a group having active hydrogen in the urethane resin with a specific compound.

[0050] The polyurethane resin having an anionic group is preferably a resin composed of a polyol having a molecular weight of 300 to 20,000, a polyisocyanate, a chain extender having a reactive hydrogen atom, a group reactive with an isocyanate group, and a compound having at least one anionic group.

[0051] In the present invention, a more preferred form of the resin component (A) is to introduce functional groups such as carboxyl groups, hydroxyl groups, methylol groups, and amide groups into the acrylic resin by copolymerization, and mix with a material capable of crosslinking with the functional groups. In this case, the use of the specific acrylic resin described above increases the reaction efficiency with the crosslinking agent, and the effect of improving the water resistance and heat resistance of the laminated film is exhibited. As the type of crosslinking agent, for example, a melamine-based crosslinking agent, an oxazoline-based crosslinking agent, an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, an aziridine-based crosslinking agent, a methylol- or alkylol-based urea-based, acrylamide-based, polyamide-based resins, amide epoxy compounds, various silane coupling agents, various titanate-based coupling agents, etc. can be used. In particular, a melamine-based crosslinking agent and an oxazoline-based crosslinking agent are preferred.

[0052] The resin layer (X) of the present invention preferably contains polystyrene sulfonic acid and / or a salt thereof. By containing polystyrene sulfonic acid and / or a salt thereof, antistatic properties can be improved.

[0053] When the resin layer (X) contains polystyrene sulfonic acid and / or a salt thereof, it is preferable that the polystyrene sulfonic acid and / or a salt thereof (B) is uniformly and finely dispersed in the matrix of the resin component (A). By uniformly and finely dispersing the polystyrene sulfonic acid and / or a salt thereof (B) in the matrix of the resin component (A), the coating film is less likely to crack, is less likely to be scraped off, transparency is not reduced, and problems such as blocking due to moisture absorption do not occur.

[0054] The method for uniformly and finely dispersing polystyrene sulfonic acid and / or a salt thereof (B) in the matrix of the resin component (A) includes the following: 1. A method of making the solubility parameter of the resin component (A) closer to that of polystyrene sulfonic acid and / or its salt (B) by selecting the molecular structure of the resin component (A); 2. Method of adding a third component having a solubility parameter intermediate between the resin component (A) and polystyrene sulfonic acid and / or its salt (B) Among these, from the viewpoint of achieving both antistatic properties and abrasion resistance, a preferred method is to add a third component having a solubility parameter intermediate between the resin component (A) in 2 and polystyrene sulfonic acid and / or its salt (B). As the third component, a solvent component that volatilizes during the manufacturing process or a resin material having a reactive site can be used. As the third component, in order to achieve both antistatic properties and abrasion resistance, it is particularly preferable that the third component is a polyhydric alcohol compound (C) described below.

[0055] Here, polystyrene sulfonic acid and / or its salts include polystyrene sulfonated and neutralized with hydroxides of monovalent alkali metals or alkaline earth metals, such as potassium, sodium, or lithium, to form metal counterions, neutralized with ammonia to form ammonium counterions, or anionic polymers obtained by polymerizing styrene sulfonic acid or styrene sulfonate salts (salts of the above metals and ammonium). It is preferable to use this polystyrene sulfonic acid and / or its salts as homopolymers in order to exert an antistatic function, but it may be copolymerized with various monomers described as constituent monomers of resin component (A).

[0056] In the laminated polyester film of the present invention, the resin layer (X) preferably contains a polyhydric alcohol compound (C), which can improve the durability of antistatic properties.

[0057] The polyhydric alcohol compound (C) in the present invention is a compound having three or more hydroxyl groups, such as pentaerythritol, dipentaerythritol, tripentaerythritol, polypentaerythritol, neopentyl glycol, trimethylolpropane, ditrimethylolpropane, 1,3,5-tris(2-hydroxyethyl)isocyanurate (THEIC), polyethylene glycol, glycerin, diglycerin, mannitol, maltitol, lactitol, sorbitol, erythritol, xylitol, xylose, sucrose, trehalose, inositol, fructose, maltose, lactose, etc. This polyhydric alcohol compound (C) is not a polymer.

[0058] Particularly preferred polyhydric alcohol compounds (C) are sugar alcohol compounds, such as sorbitol (boiling point 296° C.), xylitol (melting point 216° C.), erythritol (melting point 329 to 331° C.), mannitol (melting point 290 to 295° C.), etc. The polyhydric alcohol compounds (C) may be used alone or in combination of two or more kinds.

[0059] The polyhydric alcohol compound (C) preferably has a boiling point of 200°C or more, more preferably 220°C or more, even more preferably 240°C or more, and the upper limit is preferably 500°C or less. If the boiling point of the polyhydric alcohol compound (C) is 200°C or more, the antistatic property of the antistatic layer is further improved. On the other hand, the melting point of the polyhydric alcohol compound (C) is preferably 20°C or more. The boiling point of the hydroxyl group-containing compound can be determined by differential scanning calorimetry (DSC).

[0060] The polyhydric alcohol compound (C) has a solubility parameter (SP value) of 35 [MPa 1 / 2 ] or more, 50 [MPa 1 / 2 If the SP value is less than 35 or exceeds 50, compatibility with the resin component (A) and polystyrene sulfonic acid and / or its salt (B) becomes difficult, and abnormal aggregates tend to be generated, resulting in a decrease in the ratio R of the surface resistivity before and after the abrasion treatment.Y / R X The value of , and the ratio of surface resistivity values ​​before and after corona discharge treatment R z / R X The value of may easily exceed the preferred range.

[0061] Solubility parameters are listed, for example, in "Polymer Handbook (fourth Edition)" edited by J. BRANDRUP et al. (JOHN WILEY & SONS). On the other hand, if the solubility parameter value is not listed in the database, it can be calculated as the vector length of the three components using Hansen Solubility Parameter in Practice (HSPiP) ver. 3.1.03 (http: / / www.hansen-solubility.com / index.php) by specifying the solubility in a solvent with known parameter values ​​using the method shown in the examples, based on the nature that substances with similar solubility parameter values ​​tend to dissolve easily in each other.

[0062] The polyhydric alcohol compound (C) satisfies the following (i) and (ii): (i) Solubility parameter (SP value) is 35 [MPa 1 / 2 ] or more, 50 [MPa 1 / 2 ] or less. (ii) The boiling point is 200°C or higher. It is particularly preferred to have a sugar alcohol.

[0063] Furthermore, another laminated polyester film of the present invention is a laminated polyester film having a polyester film and a resin layer (X), the laminated polyester film having the resin layer (X) on at least one surface layer, the resin layer (X) having a resin component (A), polystyrene sulfonic acid and / or a salt thereof (B), and a polyhydric alcohol (C), and the glass transition temperature of the resin component (A) is 40°C or higher and 120°C or lower.

[0064] Another laminated polyester film of the present invention is preferably a laminated polyester film in which the resin component (A) contains at least one resin selected from the group consisting of an acrylic resin, a polyester resin, a polyurethane resin, a melamine resin and an epoxy resin.

[0065] In another laminated polyester film of the present invention, the resin component (A) has a glass transition temperature of 40° C. or more and 120° C. or less. The glass transition temperature (Tg) of the resin component (A) is preferably 60° C. or more and 120° C. or less, particularly preferably 70° C. or more and 120° C. or less.

[0066] Another laminated polyester film of the present invention contains polystyrene sulfonic acid and / or a salt thereof (B). It is preferable that polystyrene sulfonic acid and / or a salt thereof (B) is uniformly and finely dispersed in the matrix of the resin component (A).

[0067] Another laminated polyester film of the present invention contains a polyhydric alcohol (C). The polyhydric alcohol compound (C) in the present invention is a compound having three or more hydroxyl groups, and a particularly preferred polyhydric alcohol compound (C) is a sugar alcohol compound. The polyhydric alcohol compound (C) preferably has a boiling point of 200°C or higher, more preferably 220°C or higher, and even more preferably 240°C or higher. The polyhydric alcohol compound (C) has a solubility parameter (SP value) of 35 [MPa 1 / 2 ] or more, 50 [MPa 1 / 2 ] or less.

[0068] In the laminated polyester film of the present invention, the resin layer (X) preferably contains a compound (D) having an ethylene oxide group. By containing such a component, the slip property of the resin layer (X) can be improved, and the durability of the antistatic property can be improved.

[0069] In the present invention, the compound (D) having an ethylene oxide group refers to a compound having a structure represented by formula (1).

[0070] -(CH 2 -CH 2 -O) k - Formula (1) (where k represents an integer greater than or equal to 3).

[0071] Examples of the compound (D) having an ethylene oxide group include polyoxyethylene-polyoxypropylene block copolymers, polyethylene glycols, etc. Commercially available products may be used, specifically, Pluronic(R) PE3100, PE3500, PE4300, PE6100, PE6120, PE6200, PE6400, PE6800, PE7400, PE8100, PE9200, PE9400, PE10100, PE10300, PE10400, PE10500 (all manufactured by BASF Japan Co., Ltd.), ADEKA(R) "Pluronic(R)" L-23, L-31, L-33, L-34, L-35, F-38, L-42, L-43, L-44, L-61, L-62, L-64, L-66, L-68, L-69, L-70, L-71, L-72, L-73, L-74, L-75, L-76, L-77, L-78, L-79, L-81, L-82, L-83, L-84, L-85, L-86, L-87, L-88, L-89, L-90, L-91, L-92, L-93, L-94, L-95, L-96, L-97, L-98, L-99, L-100, L-101, L-102, L-103, L-104, L-105, L-106, L-107, L-108, L-109, L-200, L-201, L-202, L-203, L-204, L-205, L-2 , L-62, L-64, P-65, F-68, L-71, L-72, P-75, P-77, L-81, P-84, P-85, F-88, L-92, P-94, F-98, L-101, P-103, P-104, P-105, F-108, L-121, L-122, P-123, F-127 (all manufactured by ADEKA CORPORATION), Newpol PE-34, PE-61, PE-62, PE-64, PE-68, PE-71, PE-74, PE-75, PE-78, PE-108, PE-128 (all manufactured by Sanyo Chemical Industries, Ltd.), and the like can be used.

[0072] The weight average molecular weight of the compound (D) having an ethylene oxide group is preferably from 1000 to 20000. More preferably, it is from 2000 to 16000, even more preferably from 6000 to 16000, and particularly preferably from 11000 to 16000. By setting the weight average molecular weight to from 1000 to 20000, the dispersion stability of the resin component (A) and the polystyrene sulfonic acid and / or its salt (B) can be improved, and deterioration of the antistatic property due to wear of the resin layer can be suppressed.

[0073] In the present invention, the weight average molecular weight of the compound (D) having an ethylene oxide group is determined by measuring using gel permeation chromatography (GPC) in the manner described below. Specifically, it is calculated as the weight average molecular weight converted into standard polymethyl methacrylate under the following measurement conditions. Apparatus: Tosoh Corporation GPC apparatus (HLC-8220) Columns: TSK GEL SuperH1000, TSK GEL SuperH2000, TSK GEL SuperH3000 (both manufactured by Tosoh Corporation) Solvent: Water / ethanol Flow rate: 0.5mL / min Sample concentration: 1mg / mL Injection volume: 0.1mL.

[0074] The thickness of the resin layer (X) in the laminated polyester film of the present invention is preferably 10 to 100 nm. More preferably, it is 15 nm or more and 80 nm or less, and further preferably, it is 20 nm or more and 70 nm or less. By making the thickness of the resin layer 10 nm or more and 100 nm or less, it becomes possible to fully develop the initial antistatic property and resistance to deterioration while maintaining excellent transparency.

[0075] In the laminated polyester film of the present invention, the resin layer (X) is preferably a layer formed from a coating composition containing a resin component (A) and polystyrene sulfonic acid and / or a salt thereof (B).

[0076] The laminated polyester film of the present invention may have an intermediate layer between the resin layer (X) and the polyester film. When an intermediate layer is provided, the film may be scratched when the film having the intermediate layer laminated thereon is wound up or in the subsequent process up to the provision of the resin layer (X) of the present invention. Therefore, in the laminated polyester film of the present invention, it is preferable that the resin layer (X) and the polyester film are directly laminated.

[0077] The laminated polyester film of the present invention preferably has a haze of 5.0% or less. By setting the haze to 5.0% or less, the film can be preferably used as a protective film or a cover tape. The haze is more preferably 4.0% or less, and further preferably 3.0% or less.

[0078] The laminated polyester film of the present invention is a laminated polyester film having a polyester film and a resin layer (X). The polyester film may be a single-layer film or a laminated film. In the present invention, the polyester film refers to a component in which polyester accounts for 50% by weight or more of the total resin constituting the film.

[0079] The polyester used in the laminated polyester film of the present invention will be described below. First, polyester is a general term for polymers having ester bonds in the main chain, and preferably contains at least one component selected from ethylene terephthalate, propylene terephthalate, ethylene-2,6-naphthalate, butylene terephthalate, propylene-2,6-naphthalate, ethylene-α,β-bis(2-chlorophenoxy)ethane-4,4'-dicarboxylate, etc.

[0080] The polyester film using polyester is preferably a biaxially oriented polyester film. A biaxially oriented polyester film is generally a polyester sheet or film in an unstretched state that is stretched about 2.5 to 5.0 times in both the longitudinal direction and the width direction perpendicular to the longitudinal direction, and then heat-treated to complete crystal orientation, and shows a biaxially oriented pattern in wide-angle X-ray diffraction. When the polyester film is biaxially oriented, it has sufficient thermal stability, particularly dimensional stability and mechanical strength, and also has good flatness.

[0081] Various additives, such as antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic fine particles, fillers, antistatic agents, nucleating agents, etc., may be added to the polyester film to the extent that they do not deteriorate the properties of the polyester film.

[0082] In the present invention, the polyester film preferably contains particles. As the particle type, silica, colloidal silica, alumina, alumina sol, kaolin, talc, mica, calcium carbonate, etc. can be used as a representative particle type. The particle type and particle size may be a single material or a combination of multiple materials. In the case of a composite film by co-extrusion as described below, it is particularly preferable that the particles are contained at least in the surface layer. The total amount of the particles is preferably 0.1% by weight or less with respect to the entire polyester film. By setting the particle content within the above range, the internal haze can be set to 0.2% or less, and a film with excellent transparency can be obtained.

[0083] The thickness of the polyester film is appropriately selected depending on the application and type, but is usually preferably 5 to 500 μm, more preferably 6 to 250 μm, and most preferably 7 to 150 μm in terms of mechanical strength, handleability, etc. The polyester film may be a composite film obtained by coextrusion, or may be a film obtained by laminating the obtained films by various methods.

[0084] The laminated polyester film of the present invention is preferably obtained by applying a coating composition containing a resin component (A), polystyrene sulfonic acid and / or a salt thereof (B), and, if necessary, a polyhydric alcohol compound (C) or a compound having an ethylene oxide group (D) onto a polyester film, and, if the coating composition contains a solvent, drying the solvent to form a resin layer (X) on the polyester film.

[0085] The laminated polyester film of the present invention is preferably used for a cover tape.

[0086] The cover tape of the present invention is a laminated polyester film having a polyester film and a resin layer (X), and has the resin layer (X) on at least one surface layer, and the surface resistivity (R X ) is 10 6 Ω / □ or more, 10 12 Ω / □ or less, R X and the surface resistivity (R Y ) and R Y / R X A laminated polyester film having a value of 5.0 or less is used.

[0087] The cover tape of the present invention is a laminated polyester film having a polyester film and a resin layer (X), the resin layer (X) being on at least one surface layer, the resin layer (X) having a resin component (A), polystyrene sulfonic acid and / or a salt thereof (B), and a polyhydric alcohol (C), and the laminated polyester film used has a glass transition temperature of the resin component (A) of 40°C or higher and 120°C or lower.

[0088] The method for producing the laminated polyester film of the present invention will be described below with reference to an example.

[0089] The method for producing the laminated polyester film of the present invention includes a step of applying a coating composition to at least one side of a polyester film, followed by a stretching treatment and a heat treatment in at least one direction, and the coating composition contains polystyrene sulfonic acid and / or a salt thereof (B).

[0090] The manufacturing method of the laminated polyester film of the present invention will be described by taking as an example a case where a polyethylene terephthalate (hereinafter, PET) film is used as the polyester film. First, PET pellets are thoroughly vacuum-dried, then fed into an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to produce an unstretched (unoriented) PET film (A film). This film is stretched 2.5 to 5.0 times in the longitudinal direction with a roll heated to 80 to 120°C to obtain a uniaxially oriented PET film (B film). A coating composition prepared to a predetermined concentration is applied to one side of this B film.

[0091] The coating composition is preferably applied to the polyester film by an in-line coating method. The in-line coating method is a method in which the coating is performed within the process of manufacturing the polyester film. Specifically, the in-line coating method refers to a method in which the coating is performed at any stage from melt extrusion of the polyester resin to biaxial stretching, heat treatment, and winding up. Usually, the coating is performed on any of the following films: an unstretched (unoriented) polyester film (A film) in a substantially amorphous state obtained by melt extrusion and quenching, a uniaxially stretched (uniaxially oriented) polyester film (B film) that has been stretched in the longitudinal direction, or a biaxially stretched (biaxially oriented) polyester film (C film) that has been further stretched in the width direction and has not yet been heat-treated.

[0092] In the method for producing the laminated polyester film of the present invention, it is preferable to adopt a method in which a coating composition is applied to either the polyester film A or B before the crystal orientation is completed, and then the polyester film is stretched in a uniaxial or biaxial direction and heat-treated at a temperature higher than the boiling point of the solvent to complete the crystal orientation of the polyester film and provide a resin layer (X). According to this method, the formation of the polyester film and the coating and drying of the coating composition (i.e., the formation of the resin layer (X)) can be performed simultaneously, which is advantageous in terms of production costs. By including a polyhydric alcohol compound (C) in the coating composition, aggregation is suppressed, making it easier to obtain a high-quality stretched film.

[0093] Among these, the method of applying the coating composition to a polyester film (film B) uniaxially stretched in the longitudinal direction, then stretching the film in the transverse direction and heat treating is preferred. This is because, compared to the method of applying the coating composition to an unstretched film and then biaxially stretching the film, this method involves one less stretching step, so that defects and cracks in the composition layer due to stretching are less likely to occur, and a composition layer with excellent transparency, smoothness, and antistatic properties can be formed.

[0094] The method for producing the laminated polyester film of the present invention preferably includes the steps of applying a coating composition as the resin layer (X) to at least one surface of a polyester film, followed by stretching and heat treatment in at least one direction.

[0095] In the present invention, the resin layer (X) is preferably provided by an in-line coating method. Here, the coating method of the coating composition on the polyester film can be any known coating method, such as a bar coating method, a reverse coating method, a gravure coating method, a die coating method, a blade coating method, or the like.

[0096] The best method for forming the resin layer (X) in the present invention is to apply a coating composition using an aqueous solvent onto a polyester film by in-line coating, followed by drying and heat treatment. More preferably, the coating composition is in-line coated onto the B film after uniaxial stretching. In the method for producing the laminated polyester film of the present invention, the drying can be preferably carried out at a temperature range of 80 to 130°C in order to complete removal of the solvent from the coating composition. The heat treatment can be carried out at a temperature range of 160 to 240°C in order to complete the crystal orientation of the polyester film and the thermal curing of the coating composition to complete the formation of the resin layer (X).

[0097] By providing the resin layer (X) by the in-line coating method, the coating composition is applied, followed by a stretching treatment, which promotes the alignment of the polystyrene sulfonic acid and / or a salt thereof (B), thereby obtaining excellent antistatic performance. At the same time, the subsequent high-temperature heat treatment can improve the stability of the antistatic performance against abrasion and surface treatment.

[0098] In the method for producing a laminated polyester film of the present invention, the coating surface of the PET film may be subjected to a surface treatment such as a corona discharge treatment before coating. By performing a surface treatment such as a corona discharge treatment, the wettability of the coating composition to the PET film is improved, the coating composition is prevented from being repelled, and a resin layer (X) with a uniform coating thickness can be formed. After coating, it is preferable to hold the end of the PET film with a clip and guide it to a heat treatment zone (preheating zone) at 80 to 130 ° C. to dry the solvent of the coating composition. After drying, it is preferable to stretch the film 1.1 to 5.0 times in the width direction. It is preferable to subsequently guide the film to a heat treatment zone (thermal fixation zone) at 160 to 240 ° C. and perform heat treatment for 1 to 30 seconds to complete the crystal orientation.

[0099] In this heat treatment step (heat setting step), a relaxation treatment of 3 to 15% may be performed in the width direction or the length direction as necessary. The laminated polyester film thus obtained is a film excellent in transparency, antistatic property, and antistatic durability.

[0100] The coating composition of the present invention will now be described.

[0101] The coating composition of the present invention contains resin component (A) in an amount of 15% by weight to 75% by weight based on the total solids weight, and polystyrene sulfonic acid and / or its salt (B) in an amount of 15% by weight to 50% by weight based on the total solids weight. If the resin component (A) is less than 15% by weight, the film-forming properties of the coating film are insufficient, and not only is the durability of the antistatic performance against abrasion not obtained, but the resin layer (X) is likely to fall off from the polyester film. On the other hand, if it exceeds 75% by weight, the antistatic properties are insufficient.

[0102] In the coating composition of the present invention, polystyrene sulfonic acid and / or its salt (B) is contained in a proportion of 15% by weight to 50% by weight based on the total solid content of the coating composition. If it is less than 15% by weight, the antistatic properties are insufficient. On the other hand, if it exceeds 50% by weight, the transparency of the coating film is impaired, and the quality is reduced due to cracks and scrapes of the film.

[0103] In the coating composition of the present invention, the resin component (A) is preferably a resin selected from acrylic resins, polyester resins, polyurethane resins, melamine resins and epoxy resins.

[0104] In the coating composition of the present invention, the resin component (A) has a glass transition temperature of 40° C. or higher and 120° C. or lower. The glass transition temperature (Tg) of the resin component (A) is preferably 60° C. or higher and 120° C. or lower, particularly preferably 70° C. or higher and 120° C. or lower.

[0105] The resin component (A) contained in the coating composition of the present invention is preferably in the form of an emulsion dispersed in a water solvent.

[0106] The coating composition of the present invention preferably contains a polyhydric alcohol compound (C). In the coating composition, the polyhydric alcohol compound (C) is preferably contained in a ratio of 5% by weight to 20% by weight based on the total solids weight of the coating composition. If it is less than 5% by weight, the coating composition is likely to aggregate, and it may be difficult to obtain durability of the antistatic performance against abrasion. On the other hand, if it exceeds 20% by weight, the film-forming ability is likely to be insufficient and blocking may be likely to occur.

[0107] In the coating composition of the present invention, the polyhydric alcohol compound (C) preferably contains at least one selected from sorbitol, xylitol, maltitol, erythritol, mannitol and lactitol.

[0108] In the coating composition of the present invention, the polyhydric alcohol compound (C) satisfies the following (i) and (ii): (i) Solubility parameter (SP value) is 35 [MPa 1 / 2 ] or more, 50 [MPa 1 / 2 ] or less. (ii) The boiling point is 200°C or higher. It is preferable to have a sugar alcohol.

[0109] In the coating composition of the present invention, when the coating composition contains a solvent, it is preferable to use an aqueous solvent as the solvent (to use an aqueous coating agent). By using an aqueous solvent, it is possible to suppress the rapid evaporation of the solvent during the drying process, and it is not only possible to form a uniform composition layer, but also it is excellent in terms of environmental load.

[0110] Here, the aqueous solvent refers to water or a mixture of water and a water-soluble organic solvent, such as alcohols (e.g., methanol, ethanol, isopropyl alcohol, butanol, etc.), ketones (e.g., acetone, methyl ethyl ketone, etc.), or glycols (e.g., ethylene glycol, diethylene glycol, propylene glycol, etc.), in any ratio.

[0111] The coating composition of the present invention preferably contains a compound (D) having an ethylene oxide group. The inclusion of the compound (D) having an ethylene oxide group makes it easier to suppress the occurrence of aggregation, and as a result, makes it easier to suppress the deterioration of antistatic properties due to wear, which is a problem of the resin layer of the present invention. Whether the coating composition contains a compound (D) having an ethylene oxide group can be measured using time-of-flight secondary ion gravimetric spectrometry (GCIB-TOF-SIMS) under the measurement conditions described below.

[0112] The compound (D) having an ethylene oxide group is preferably contained in a proportion of 2% by weight or more and 20% by weight or less based on the total solid weight of the coating composition. If it is less than 2% by weight, aggregation is likely to occur, and the transparency and quality of the coating film may decrease. On the other hand, if it is 20% by weight, foaming may occur and the coating appearance may deteriorate.

[0113] In the coating composition of the present invention, the weight average molecular weight of compound (D) is preferably 1,000 or more and 20,000 or less.

[0114] The coating composition of the present invention is preferably a laminated polyester film having a polyester film and a resin layer (X), which has a resin layer (X) on at least one surface layer, and the surface resistivity (R X ) is 10 6 Ω / □ or more, 10 12 Ω / □ or less, R X and the surface resistivity (R Y ) and R Y / R X The resin layer (X) of the laminated polyester film is formed so that the value of

[0115] The coating composition of the present invention preferably forms the resin layer (X) of a laminated polyester film having a polyester film and a resin layer (X), the resin layer (X) being on at least one surface layer, the resin layer (X) comprising a resin component (A), polystyrene sulfonic acid and / or a salt thereof (B), and a polyhydric alcohol (C), and the glass transition temperature of the resin component (A) is 40°C or higher and 120°C or lower.

[0116] [Methods of measuring characteristics and evaluating effects] The methods for measuring the characteristics and evaluating the effects of the present invention are as follows.

[0117] (1) Surface resistivity Surface resistivity R X The measurement was carried out after leaving the sample at 23°C and 65% relative humidity for 24 hours, and then using a digital ultra-high resistance / micro ammeter R8340A (manufactured by Advantest Corporation) in that atmosphere, applying a voltage of 100V for 10 seconds. The unit is Ω / □. The resin laminate surface of the laminate sample was evaluated, and the average value of a total of 10 measurements was taken as the surface resistivity R of the sample. X It was decided.

[0118] (2) Surface resistivity after abrasion Surface resistivity R after wear Y The measurement was carried out according to the following procedure. First, the resin layer (X) of the laminated polyester film was fixed to a Haydon Tribogear TYPE:38 manufactured by Shinto Scientific Co., Ltd. so that the surface to be abraded faced upwards. Next, a nonwoven fabric (Hi-Ze Gauze NT-4 manufactured by Ozu Sangyo Co., Ltd.) was attached to the ASTM flat indenter. The measurement was then performed over a travel distance of 100 mm, a travel speed of 2000 mm / min, and a load of 20 g / cm. 2 The surface of the resin layer (X) was abraded 10 times under the above conditions. Then, the surface resistivity R X The measurement was carried out in the same manner as in Example 1. The unit is Ω / □. The resin laminate surface of the laminated sample was evaluated, and the average value of a total of 10 measurements was taken as the surface resistivity R of the sample after abrasion. Y It was decided.

[0119] (3) Surface resistivity after corona discharge treatment Surface resistivity R after corona discharge treatment Z The measurement of was carried out by the following procedure. First, the laminated polyester film was cut into a size of 10 cm x 20 cm. Next, using a corona surface modification evaluation device TEC-4AX manufactured by Kasuga Electric Co., Ltd., the laminated polyester film was placed on an earth plate with the resin layer (X) facing upward, and corona discharge treatment was carried out under the following conditions: corona discharge treatment output 100 W, discharge gap with the ceramic electrode 1 mm, electrode moving speed 0.5 m / min, and treatment number 1. Next, the above-mentioned surface resistivity value R X The measurement was carried out in the same manner as in Example 1. The unit is Ω / □. The resin laminate surface of the laminate sample was evaluated, and the average value of a total of 10 measurements was taken as the surface resistivity R of the sample after corona discharge treatment. Z It was decided.

[0120] (4) Center line average roughness The surface of the resin layer (X) was measured using the following device and conditions to obtain the center line average roughness Ra defined in JIS R1683 (2007). Measurement equipment: Atomic force microscope (AFM) manufactured by Burker Corporation Measurement mode: Tapping mode Cantilever: Bruker AXS SCANASYST-AIR (Material: Si, spring constant K: 0.4 (N / m), tip curvature radius R: 2 (nm)) Measurement atmosphere: 23℃ in air Measurement range: 1 (μm) square Resolution: 512×512.

[0121] Specifically, the measured data from the Height Sensor channel was analyzed using "NanoScope Analysis V1.40", smoothed using Plane Fit (XY, 3rd), and then processed using Roughness. The Ra value in the Results tab was used as the surface centerline average roughness Ra of the resin layer (X).

[0122] (5) Coefficient of kinetic friction Based on JIS K7125 (1999), the dynamic friction coefficient of both sides of the laminated polyester film was measured using a HEIDON-14DR-ANL device (manufactured by Shinto Scientific Co., Ltd.) with a contact area of ​​4 cm 2 The measurements were taken at a load of 1.96 N and a speed of 100 mm / min. The average value of the friction resistance from 1 second after the start of the measurement to the end of the measurement was taken as the kinetic friction force from the chart measured for 4 seconds (data recorded every 2.0 msec), and this was divided by the area and weight to obtain the kinetic friction coefficient.

[0123] (6) Hayes The haze was measured by leaving the sample for 40 hours under normal conditions (23°C, relative humidity 50%) and then using a turbidity meter "NDH5000" manufactured by Nippon Denshoku Industries Co., Ltd., in accordance with JIS K 7136 "Determining the haze of transparent materials" (2000 edition). The measurement was performed by irradiating light from the side where the sample surface α was laminated. Ten square samples with sides of 50 mm were prepared, and each was measured once, for a total of 10 times, and the average value was taken as the haze value of the sample.

[0124] (7) Thickness of resin layer The thickness of the resin layer on the polyester film was measured by observing the cross section using a transmission electron microscope (TEM). The thickness of the resin layer was read from an image taken with a TEM at a magnification of 200,000 times. The thickness of the resin layer was measured at a total of 10 points and the average value was calculated.

[0125] (8) Presence or absence of resin component (A), polystyrene sulfonic acid and / or its salt (B), and polyhydric alcohol compound (C) The composition of the resin layer was analyzed by X-ray photoelectron spectroscopy (ESCA), Fourier transform infrared spectroscopy (FT-IR) ATR method, and time-of-flight secondary ion mass spectrometry (TOF-SIMS) on the surface of the resin layer (X). In addition, the resin layer (X) was dissolved and extracted with a solvent, separated by chromatography, and then analyzed by proton nuclear magnetic resonance spectroscopy ( 1 H-NMR), Carbon Nuclear Magnetic Resonance Spectroscopy ( 13 The structure was analyzed using C-NMR and Fourier transform infrared spectroscopy (FT-IR), and pyrolysis gas chromatography-gravimetric analysis (GC-MS) was performed to examine the presence or absence of resin component (A), polystyrene sulfonic acid and / or its salt (B), and polyhydric alcohol compound (C).

[0126] In Tables 5 and 6, the resin layer is marked with Y when it contains the structure of the polyhydric alcohol compound (C), and marked with N when it does not contain the structure.

[0127] (9) Glass transition temperature Tg of resin component (A) The glass transition temperature (Tg) of the resin component (A) was measured by weighing 3 mg of a sample in a sample pan using a differential scanning calorimeter (DSC) (Hitachi High-Tech Science Corporation; thermal analyzer DSC / 6220). In the first run, the sample was heated from 25°C to 200°C at 20°C / min, and then rapidly cooled to 25°C. In the second run, the glass transition temperature was calculated from the intersection point of a line equidistant from the extended line of each baseline in the vertical axis direction and the curve of the stepwise change part of the glass transition in the differential scanning calorimeter measurement chart (vertical axis is thermal energy, horizontal axis is temperature) during the temperature increase process (2nd RUN) from 25°C to 200°C at 20°C / min. When two or more stepwise change parts of the glass transition were observed, the glass transition temperature was calculated for each of them, and the average value of these temperatures was used as the glass transition temperature (Tg) (°C) of the sample.

[0128] (10) Presence or absence of a compound (D) having an ethylene oxide group The composition of the resin layer surface of the laminated film was analyzed using GCIB-TOF-SIMS (GCIB: Gas Cluster Ion Beam, TOF-SIMS: Time-of-Flight Secondary Ion Gravimetric Analysis). The measurement conditions were as follows. <Sputtering conditions> Ion source: Argon gas cluster ion beam <Detection conditions> Primary ion: Bi3++(25keV) Secondary ion polarity: Negative Mass range: m / z 0~1000 Measurement range: 200 x 200 μm 2 The peak intensity of the fragment detected at the maximum intensity is K, the fragment derived from the repeating structure of ethylene oxide group (-(CH 2 -CH 2 -O-CH 2 -CH 2 -O-CH 2 -CH 2The peak intensity of the ethylene oxide group-containing compound (D) was designated as Q, and when Q / K≧0.02, the resin layer was determined to contain a compound (D) having an ethylene oxide group. In Tables 35 and 36, when the resin layer contains a compound (D) having an ethylene oxide group, it is designated Y, and when it does not contain D, it is designated N.

[0129] (11) Weight average molecular weight of compound (D) having an ethylene oxide group The weight average molecular weight of the compound (D) having an ethylene oxide group is determined by measuring using gel permeation chromatography (GPC). Specifically, the weight average molecular weight was calculated as the weight average molecular weight converted into standard polymethyl methacrylate under the following measuring conditions.

[0130] Apparatus: Tosoh Corporation GPC apparatus (HLC-8220) Columns: TSK GEL SuperH1000, TSK GEL SuperH2000, TSK GEL SuperH3000 (both manufactured by Tosoh Corporation) Solvent: Water / ethanol Flow rate: 0.5mL / min Sample concentration: 1mg / mL Injection volume: 0.1mL.

[0131] (12) Blocking property (peelability after blocking test) The laminated film was cut into a 5 cm square. The laminated film was laminated so that the A layer surface and the B layer surface were in contact with each other, and then processed for 5 hours at 50°C under a load of 150 kgf using a C-type heatable 60 ton press (manufactured by Gonno Hydraulic Machinery Co., Ltd.). The blocking property was evaluated based on the resistance when the sample after processing in which two laminated films were stacked was peeled off with tweezers, using the following criteria. 4: Extremely little resistance when peeling off. 3: There is almost no resistance during peeling, and no interlayer delamination occurs in the peeled laminate film. 2: There is resistance during peeling, but there is no delamination of the peeled laminate film. 1: Interlayer delamination between layers A and B has occurred in at least one of the peeled laminated films. EXAMPLES

[0132] The laminated polyester film of the present invention will be described in detail below with reference to specific examples, but the present invention is not limited to these examples.

[0133] First, a resin composition A was prepared as follows. A-1: An emulsion solution of acrylic resin (emulsion diameter 50 nm) with a Tg of 46°C, consisting of methyl methacrylate (47 mol%), ethyl acrylate (45 mol%), acrylic acid (2 mol%), N-methylol acrylamide (1 mol%), polyethylene glycol monomethacrylate with 16 ethylene oxide repeating units (3 mol%), and 2-sulfoethyl acrylate (2 mol%). A-2: An emulsion solution of acrylic resin (emulsion diameter 50 nm) with a Tg of 67°C consisting of methyl methacrylate (66 mol%), ethyl acrylate (30 mol%), acrylic acid (3 mol%), and N-methylol acrylamide (1 mol%).

[0134] Aqueous solutions of the other components were prepared as follows. The mixing ratios of each coating composition are shown in Tables 1 and 2. A-3: An emulsion solution of acrylic resin (emulsion diameter 50 nm) with a Tg of 79°C, consisting of methyl methacrylate (76 mol%), ethyl acrylate (20 mol%), acrylic acid (3 mol%), and N-methylol acrylamide (1 mol%) A-4: An emulsion solution of acrylic resin (emulsion diameter 50 nm) with a Tg of 90°C, consisting of methyl methacrylate (84 mol%), methyl acrylate (11 mol%), acrylic acid (4 mol%), and N-methylol acrylamide (1 mol%) B-1: Aqueous solution of polystyrene sulfonate ammonium salt (weight average molecular weight 70,000) B-2: 49 parts by weight of 1% by weight iron (III) sulfate aqueous solution, 8.8 parts by weight of 3,4-ethylenedioxythiophene, and 117 parts by weight of 10.9% by weight peroxodisulfuric acid aqueous solution were added to 1887 parts by weight of an aqueous solution containing 20.8 parts by weight of polystyrenesulfonic acid. This mixture was stirred at 18°C ​​for 23 hours. Next, 154 parts by weight of a cation exchange resin and 232 parts by weight of an anion exchange resin were added to this mixture, and after stirring for 2 hours, the ion exchange resin was filtered off to obtain an aqueous dispersion B-2 (solid concentration 1.3% by weight) of a mixture consisting of poly(3,4-ethylenedioxythiophene) and polystyrenesulfonic acid. C-1: Sorbitol (boiling point: 296°C, SP value: 35.8MPa) 1 / 2 ) in water C-2: Xylitol (boiling point: 216℃, SP value: 36.0MPa) 1 / 2 ) in water C-3: Erythritol (boiling point: 400℃, SP value: 33.8MPa) 1 / 2 ) in water C-4: Ethylene glycol (boiling point: 197°C, SP value: 33.0MPa 1 / 2 ) in water D-1: Aqueous solution of ADEKA Corporation's ADEKA (R) "Pluronic (registered trademark)" F-108 (weight average molecular weight 15,500) D-2: Aqueous solution of ADEKA Corporation's ADEKA (R) "Pluronic (registered trademark)" F-68 (weight average molecular weight 8350) D-3: Aqueous solution of ADEKA (R) "Pluronic (registered trademark)" F-88 (weight average molecular weight 10,800) manufactured by ADEKA Corporation.

[0135] Example 1 <Paint composition> As a coating composition 1 for forming the resin layer (X), an aqueous dispersion composed of A1 / B1 / C1=60 / 30 / 10 (weight ratio of solid contents) was prepared. <Laminated polyester film> PET pellets containing 0.005% by weight of colloidal silica with an average particle size of 1.5 μm were thoroughly vacuum-dried, fed into an extruder, melted at 285°C, extruded from a T-shaped die into a sheet, and wrapped around a mirror-finished casting drum with a surface temperature of 25°C using an electrostatic casting method, where it was cooled and solidified. This unstretched film was heated to 90°C and stretched 3.4 times in the longitudinal direction to produce a uniaxially stretched film (film B).

[0136] Next, the coating composition 1 was applied to the corona discharge-treated surface of the uniaxially stretched film using a bar coater. The uniaxially stretched film to which the coating composition was applied was held at both ends in the width direction with clips and introduced into a preheating zone, and the atmospheric temperature was set to 75°C. The atmospheric temperature was then set to 110°C using a radiation heater, and then to 90°C, to dry the coating composition and form a resin layer (X). The film was then continuously stretched 3.5 times in the width direction in a heating zone (stretching zone) at 120°C, and then heat-treated for 20 seconds in a heat treatment zone (thermal fixation zone) at 230°C to obtain a laminated polyester film with completed crystal orientation. The thickness of the PET film and the thickness of the resin layer (X), measured by observing the cross section of the obtained laminated polyester film using a transmission electron microscope (TEM), were 20 μm and 60 nm, respectively. The properties of the obtained laminated polyester film are shown in Tables 3 and 5.

[0137] Example 2 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-2 / B-1 / C-1 = 60 / 30 / 10 (solids weight ratio) was prepared as coating composition 2.

[0138] Example 3 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-1 = 75 / 15 / 10 (solids weight ratio) was prepared as coating composition 3.

[0139] Example 4 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-1 = 50 / 40 / 10 (solids weight ratio) was prepared as coating composition 4.

[0140] ( Example 5 ) A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 = 70 / 30 (solids weight ratio) was prepared as coating composition 5.

[0141] ( Example 6 ) A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-2 / C-1 = 60 / 30 / 10 (solids weight ratio) was prepared as coating composition 6.

[0142] Example 7 Under the conditions described in Example 1, coating composition 7 was prepared by adding 20 parts by weight of colloidal silica dispersion "Spherica 140" (silica particles, particle size 140 nm) manufactured by Catalysts and Chemical Industries, Ltd. to an aqueous dispersion composed of A-1 / B-1 / C-1 = 70 / 20 / 10 (solids weight ratio) per 100 parts by weight of the total solids weight of A-1 / B-1 / C-1, and a laminated polyester film was obtained in the same manner as in Example 1.

[0143] Example 8 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, pellets not containing colloidal silica were used as the PET pellets for the laminated polyester film.

[0144] Example 9 A laminated polyester film was obtained by the following method using the coating composition described in Example 1. A PET film "Lumirror T60" (substrate thickness 38 μm) manufactured by Toray Industries, Inc. was used as the substrate. The coating composition was applied onto the substrate using a wire bar, and then heated and cured in a hot air oven at 200°C for 1 minute. In the obtained laminated polyester film, the PET film had a thickness of 38 μm, and the resin layer had a thickness of 80 nm.

[0145] Example 10 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-2 = 60 / 30 / 10 (solids weight ratio) was prepared as coating composition 8.

[0146] Example 11 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-3 = 60 / 30 / 10 (solids weight ratio) was prepared as coating composition 9.

[0147] Example 12 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-4 = 60 / 30 / 10 (solids weight ratio) was prepared as coating composition 10.

[0148] Example 13 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-1 / D-1 = 55 / 30 / 10 / 5 (solids weight ratio) was prepared as coating composition 11.

[0149] Example 14 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-1 / D-2 = 55 / 30 / 10 / 5 (solids weight ratio) was prepared as coating composition 12.

[0150] Example 15 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-1 / D-3 = 55 / 30 / 10 / 5 (solids weight ratio) was prepared as coating composition 13.

[0151] (Example 16) A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-3 / B-1 / C-1 = 60 / 30 / 10 (solids weight ratio) was prepared as coating composition 16.

[0152] (Example 17) A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-4 / B-1 / C-1 = 60 / 30 / 10 (solids weight ratio) was prepared as coating composition 17.

[0153] (Example 18) A laminated polyester film was obtained in the same manner as in Example 9, except that the thickness of the resin layer was 60 nm.

[0154] (Example 19) A laminated polyester film was obtained in the same manner as in Example 1, except that the thickness of the resin layer was 150 nm.

[0155] Comparative Example 1 A laminated polyester film was obtained by the following method using the coating composition 5 described in Example 5. A PET film "Lumirror T60" (substrate thickness 38 μm) manufactured by Toray Industries, Inc. was used as the substrate. The coating composition was applied onto the substrate using a wire bar, and then heated and cured in a hot air oven at 200°C for 1 minute. In the obtained laminated polyester film, the PET film had a thickness of 38 μm, and the resin layer had a thickness of 80 nm.

[0156] Comparative Example 2 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-1 = 85 / 5 / 10 (solids weight ratio) was prepared as coating composition 14.

[0157] Comparative Example 3 A laminated polyester film was obtained in the same manner as in Example 1, except that, under the conditions described in Example 1, an aqueous dispersion composed of A-1 / B-1 / C-1 = 30 / 60 / 10 (solids weight ratio) was prepared as coating composition 15.

[0158] [Table 1]

[0159] [Table 2]

[0160] [Table 3]

[0161] [Table 4]

[0162] [Table 5]

[0163] [Table 6]

[0164] In the table, E represents an exponent. For example, 1.0E+09 is 1.0×10 9 Represents. [Industrial Applicability]

[0165] The laminated polyester film of the present invention is excellent in antistatic properties and in maintaining the antistatic properties during abrasion and corona discharge treatment. The laminated polyester film of the present invention can be used in various tapes, particularly for magnetic recording materials, electrical insulating materials, insulating tapes, electrical materials, optical applications such as protective films, graphics, cards, transfer foils, ribbons, deposition, packaging, capacitors, and cover tapes.

[0166] The laminated polyester film of the present invention can be preferably used for a carrier tape since it can solve problems such as dust adhesion due to peeling electrification, electrical destruction of electronic components, and further deterioration of antistatic properties and deterioration of transparency in harsh environments. Also, the laminated polyester film of the present invention can be used for a protective film since it can solve problems of a protective film such as dust adhesion due to peeling electrification, destruction of electronic elements of a display due to peeling electrification, and deterioration of antistatic properties in harsher environments.

Claims

1. A laminated polyester film having a polyester film and a resin layer (X), the resin layer (X) being on at least one surface layer, the resin layer (X) having a resin component (A), the resin component (A) having a glass transition temperature (Tg) of 46° C. or more and 120° C. or less, the resin component (A) being an acrylic resin, the resin layer (X) further having polystyrene sulfonic acid and / or a salt thereof (B), the amount of polystyrene sulfonic acid and / or a salt thereof (B) in the resin layer (X) being 15 mass % or more and 50 mass % or less, and the surface resistivity (R X ) is 10 6 Ω / □ or more, 10 12 Ω / □ or less, R X and the surface resistivity (R Y ) Ratio R Y / R X A laminated polyester film having a value of 5.0 or less. [Abrasion treatment conditions] The surface of the resin layer (X) of the laminated polyester film was subjected to a load of 20 g / cm 2 The surface of the resin layer (X) is abraded ten times with a nonwoven fabric (Hi-Ze Gauze NT-4 manufactured by Ozu Sangyo Co., Ltd.) at 100° C.

2. Surface resistivity of laminated polyester film (R X ) and the surface resistivity (R Z ) and the ratio R Z / R X The laminated polyester film according to claim 1 , wherein the linear modulus is 10.0 or less. [Corona discharge treatment conditions] The laminated polyester film is placed on an earth plate with the resin layer (X) facing upward, and a corona discharge treatment is performed on the side opposite to the side having the resin layer (X) with a corona discharge treatment output of 100 W, a discharge gap with the ceramic electrode of 1 mm, an electrode moving speed of 0.5 m / min, and a treatment number of one time.

3. 3. The laminated polyester film according to claim 1, wherein the resin layer (X) has a centerline average surface roughness Ra of 3 nm or more and 10 nm or less.

4. 4. The laminated polyester film according to claim 1, wherein a dynamic friction coefficient between the surface of the resin layer (X) and the opposite surface of the laminated polyester film is 0.5 or less.

5. 5. The laminated polyester film according to claim 1, wherein the resin layer (X) contains a polyhydric alcohol compound (C).

6. The laminated polyester film according to claim 5 , wherein the polyhydric alcohol compound (C) contains a sugar alcohol that satisfies the following (i) and (ii): (i) Solubility parameter (SP value) is 35 [MPa 1/2 ] or more, 50 [MPa 1/2 ]or less. (ii) The boiling point is 200°C or higher.

7. 7. The laminated polyester film according to claim 5, wherein the polyhydric alcohol compound (C) comprises at least one selected from the group consisting of sorbitol, xylitol, maltitol, erythritol, mannitol and lactitol.

8. The laminated polyester film according to claim 1 , which is used for a cover tape.

9. A cover tape using the laminated polyester film according to any one of claims 1 to 8.

10. A method for producing a laminated polyester film according to any one of claims 1 to 8, comprising the steps of applying a coating composition to at least one side of a polyester film, followed by stretching and heat treatment in at least one direction, wherein the coating composition contains polystyrene sulfonic acid and / or a salt thereof (B).

Citation Information

Patent Citations

  • Biaxially oriented polyester film

    JP1986204240A

  • Laminated polyester film

    JP2003071995A

  • Laminated film and manufacturing process thereof

    JP2004058648A

  • Cover tape

    JP2010013135A

  • Laminate polyester film

    JP2015208906A